Trends in analgesia in prehospital trauma care: an analysis of 105.908 patients from the multicenter database TraumaRegister DGU® - Uzun, Davut D.; Stock, Jan-Philipp; Steffen, Richard; Knapp, Jürgen; Lefering, Rolf; Schmitt, Felix; Weigand, Markus A.; Münzberg, Matthias; Woelfl, Christoph G.; Häske, David (BMC emergency medicine, 2025)
The management of pain in patients with traumatic injuries is a common task for emergency medicine providers, particularly in the prehospital setting. However, for sufficient and safe analgesia, correct pain recording and documentation is also necessary. The aim of this study was to assess trends in analgesia over the study period and to identify factors that may enable more sufficient pain management in trauma care. The TraumaRegister DGU® recorded data of patients who were primarily treated at one of the participating hospitals between 2011 and 2020 and received analgesia as part of their prehospital care. This retrospective analysis included a total of 105.908 severely injured patients from Germany, Switzerland, and Austria. Patients with and without analgesia were compared, and factors associated with analgesia were investigated with logistic regression analysis. The mean age of the patients enrolled was 50 ± 22 years. 71% were male and 29% were female. Out of all the patients, 66% (n = 70,257) received prehospital analgesia. The average age of patients in the analgesia group was 48 ± 21 years, the non-analgesia group had an average age of 54 ± 23 years. 67% of the male patients received analgesia compared to 64% of the female patients. The mean Injury Severity Score (ISS) in the analgesia group was 21.2 points, compared to 16.5 points in the non-analgesia group. 4% of the patients were under the age of sixteen, and of these, 65% received analgesia. 29% of patients were older than 65 years and received analgesia in 57%. Presence of an emergency physician at scene, was a remarkable independent variable for the receipt of analgesia (Odds Ratio 5.55; p < 0.001). Transportation by helicopter was also a significant predictor for analgesia (OR 1.62; p < 0.001). Analgesia is a crucial aspect of emergency medicine, as evidenced by relevant guidelines. Nevertheless, it is plausible that a considerable proportion of seriously injured patients do not receive optimal analgesic treatment, or at the very least, this is not documented. In this regard, both aspects require optimization.
Im Titel erscheint ® hochgestellt
Gesehen am 03.09.2025